2018
DOI: 10.1007/s00192-018-3683-6
|View full text |Cite
|
Sign up to set email alerts
|

The urinary microbiome in women with mixed urinary incontinence compared to similarly aged controls

Abstract: Introduction & Hypothesis Previous studies have suggested that women with urinary incontinence have an altered urinary microbiome. We hypothesized that the microbiome in women with mixed urinary incontinence (MUI) differed from controls and tested this hypothesis using bacterial gene sequencing techniques. Methods This multicenter study compared the urinary microbiome in women with MUI and similarly aged controls. Catheterized urine samples were obtained; v4–6 regions of the 16S rRNA gene were sequenced to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
81
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 32 publications
10
81
0
3
Order By: Relevance
“…Well over half of this cohort of well‐characterised continent adult women exhibited a detectable urobiome, most commonly of the Lactobacillus urotype. This is consistent with other studies that have shown that Lactobacillus is common in the bladders of adult women with and without lower urinary symptoms . It is not surprising that Lactobacillus predominates the urobiome of many adult women, given the beneficial role that Lactobacillus generally plays in other microbial niches, and the evidence that certain Lactobacillus species are associated with a lack of lower urinary tract symptoms and reduce the risk of post‐surgical UTI , .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Well over half of this cohort of well‐characterised continent adult women exhibited a detectable urobiome, most commonly of the Lactobacillus urotype. This is consistent with other studies that have shown that Lactobacillus is common in the bladders of adult women with and without lower urinary symptoms . It is not surprising that Lactobacillus predominates the urobiome of many adult women, given the beneficial role that Lactobacillus generally plays in other microbial niches, and the evidence that certain Lactobacillus species are associated with a lack of lower urinary tract symptoms and reduce the risk of post‐surgical UTI , .…”
Section: Discussionsupporting
confidence: 91%
“…The variability of the urobiome, in terms of urotype, has been reported previously . The most common urotype, Lactobacillus , did not show strong correlations with specific demographic features, including age, menopausal status, parity, and vaginal intercourse.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…В настоящее время ведутся очень активно исследования микробиома мочевых путей, поскольку они должны помочь в понимании глубоких механизмов взаимодействия микро-и макроорганизма и, как следствие, в разработке новых, более точных диагностических критериев и эффективных методов терапии ИМП. Несмотря на то что большое количество исследований посвящено изучению микробиома мочевого пузыря [6,7], а верхние мочевые пути в данном направлении пока не изучены в связи с очевидными техническими сложностями, практически не вызывает сомнения тот факт, что микроорганизмы присутствуют в мочевых путях на всем их протяжении.…”
unclassified